Coopérations, territoires et entreprises agroalimentaires - Fourcade , Colette; Muchnik , José; Treillon , Roland (éditions Quae, 2010)
The Cota, territorialised food-processing cooperation partnerships, are made up of groups of SME which apply pioneering collective strategies to improve their competitiveness by using the region as a decisive variable. The study of some fifteen cases suggests two analysis paths. The first covers the building up of these new forms of cooperation by highlighting organisational trajectories. The second puts forward thoughts on the role of the territory variable in the Cota dynamics through original territorialisation strategies. The Cota are not just an analysis tool for new forms of cooperation in the food-processing industry. They are also of interest politically, as they constitute an experimental laboratory for public action by putting forward outline recommendations for good support practices.